Utilização de peptídeos sintéticos derivados de moléculas imunodominantes de Toxoplasma gondii para diagnóstico sorológico da toxoplasmose em ovinos e galinhas caipiras - Paiva, Vinícius Fernandes de (2016)
Chapter I - The obligate intracellular parasite Toxoplasma gondii is the causative agent of toxoplasmosis, a disease that affects humans and generates economic losses in farm animals. When prevention fails disease refers to the diagnosis and subsequent treatment if the individual is diagnosed as positive. Therefore, the development of new accurate diagnostic tools for detecting T. gondii infection is a need in particular to determine the environmental source of infection which can result in more appropriate public health policies against different routes of infection and prevent potential damage that toxoplasmosis can cause when animals are infected. Chapter II - The domestic chicken (Gallus gallus domesticus) are considered epidemiological sentinels, still representing a major source of recombinant strains when predated by cats, it is common to find them with multiple infections. We evaluate the diagnostic potential of six synthetic peptides (SAG2Y, MIC1, M2AP, GRA10, ROP2 and ROP7) predicted in silico from tachyzoites immunodominant markers of T. gondii in samples from naturally infected chickens, comparing synthetic peptides with antigen total soluble (STAg). In general, our results demonstrated that reactivity rates and positivity for these peptides are similar to the STAg, and the ROP7 peptide and the combination of peptides MIC1+ROP2 have significant sensitivity, confirming them as potential diagnostic tools for the diagnosis of toxoplasmosis in chickens. Chapter III - Sheep (Ovis aries) are commonly infected with Toxoplasma gondii due to his eating habits. Infection in pregnant sheep can have serious consequences such as embryonic death, fetal resorption, mummification, and neonatal death. One concern regarding the infection in these animals is that the meat can be a source of contamination to humans and other carnivores. Therefore perform accurate diagnosis in these animals is of fundamental importance. In the present study we evaluated the potential of new synthetic peptides as a diagnostic tool. Synthetic peptides (SAG2Y, SRS52A, MIC14, GRA4, GRA10 and GRA15) were predicted in silico from immunodominant proteins of T. gondii. We determine the levels of IgG antibodies using sera obtained from two farms in the city of Uberlândia. Analyzing the results together, the peptide combination GRA10+GRA15 (Accuracy = 0,82) showed better characteristics compared with the other mixtures. This preparation could be better analyzed with an antigenic mixture potential use in the diagnosis of toxoplasmosis in sheep and other species.